DETEKSI PENYAKIT BERBASIS Convolutional Neural Network (CNN) DAN PENINJAUAN KESUBURAN TANAH SEBAGAI UPAYA PENINGKATAN HASIL TANAMAN KOPI ROBUSTA DI DESA LOK-TUNGGUL KABUPATEN BANJAR - Muhammad Helmy Abdillah; Yazid Aufar; Jiki Romadoni (Jurnal Abdi Insani, 2023)
"Gerakan Tanam Kopi Serempak" (GERTAK) The Simultaneous Coffee Planting Movement Program (GERTAK) initiated by the Provincial Government of South Kalimantan has encouraged the rise of coffee MSMEs. The upstream and downstream sectors facilitated by the government can encourage the formation of a spirit of independence for young people in entrepreneurship. However, the problem upstream is that knowledge of coffee cultivation techniques still needs to be improved. It's due to the need for more practical literacy in coffee cultivation compared to other plantation crops, so academics must be involved in disseminating knowledge and technology to maximize their business. This activity aims to provide an understanding and practical solutions to disease attacks and soil management through IoT-based disease detection trials and surveys of soil fertility to increase coffee crop yields. Participants can use IoT-based disease detection and manage soil nutrients based on the results of the soil sampling unit. The activity was carried out through the Service-Learning approach (method). This approach uses four principles: engagement, reflection, reciprocity, and public dissemination, each reflected in problem identification activities in the region, discussion groups, field trials, and material delivery. The results of the activity showed the participants' interest in applying CNN-based Disease Detection Apps for Coffee technology. In addition, monitoring soil fertility through a soil sampling unit technique can assist farmers in providing precise and measurable fertilizers and organic matter. Material controlling plant pests and managing soil fertility are important parts that must be applied to increase coffee crop yields. Four main diseases originate from fungi that attack coffee plants, while the results of a soil fertility survey indicate that the soil is infertile. The activity evaluation results showed that the participants' satisfaction level was 68 points. The marketing aspect of finished products (ground coffee) still needs to be solved and requires training as a curation measure for MSMEs.